Differential expression of androgen receptor variants in hormone‐sensitive prostate cancer xenografts, castration‐resistant sublines, and patient specimens according to the treatment sequence. Issue 9 (18th April 2019) - Honda, Mariko; Kimura, Takahiro; Kamata, Yuko; Tashiro, Kojiro; Kimura, Shoji; Koike, Yusuke; Sato, Shun; Yorozu, Takashi; Furusato, Bungo; Takahashi, Hiroyuki; Kiyota, Hiroshi; Egawa, Shin
Abstract: Background: Androgen receptor variants (AR‐vs), especially AR‐v7 and AR‐v 5, 6, and 7 exon‐skipped (AR‐v567es), are reportedly key players in the development of castration‐resistant prostate cancer (CRPC). We previously established a mouse xenograft model (JDCaP) from a metastatic skin lesion from a Japanese patient with CRPC and that was revealed to exhibit androgen sensitivity. In the present study, we established multiple castration‐resistant xenograft models from JDCaP mice to investigate the biological features of CRPC. Methods: Tissue from JDCaP mice was transplanted into male and female nude mice, and after serial passaging, castration‐resistant sublines (JDCaP‐CR2M and JDCaP‐CR4M in male mice, JDCaP‐CR2F and JDCaP‐CR4F in female mice) were established. We investigated anti‐androgen and testosterone sensitivity and the messenger RNA expression pattern of full‐length AR and AR‐vs. In addition, we compared AR protein levels of patient specimens among primary, local‐recurrent, and two skin‐metastatic tumors. Results: All JDCaP‐CR sublines showed continuous growth following the administration of bicalutamide, although the effects of testosterone varied among sublines. Parental JDCaP and JDCaP‐CR2M, JDCaP‐CR4M, and JDCaP‐CR4F sublines expressed AR‐v7, whereas JDCaP‐CR2F exhibited elevated AR‐v567es expression resulting from genomic deletion, which was confirmed by DNA sequencing. Moreover, we confirmed AR‐v7 expression in the tumor of the original patient after androgen‐deprivation therapy. Conclusions: Each JDCaP‐CR subline showed different AR‐v‐expression patterns, with JDCaP‐CR2F expressing AR‐v567es due to genomic deletion. Our results indicated that AR‐vs emerged after androgen‐deprivation therapy and appeared essential for acquisition of castration resistance.